Invasive alien species Epilobium adenocaulon Hausskn. in the Republic of Karelia ... - Kravchenko, Alexei; Rudkovskaya, Oksana; Timofeeva, Vera (Karelian Research Centre of the Russian Academy of Sciences, 2021)
The dataset includes data on invasive alien vascular plants species Epilobium adenocaulon Hausskn. on the territory of the Republic of Karelia, Russia. The data set is based on collected specimens. Collected specimens are stored at the Herbarium of KarRC RAS, city of Petrozavodsk (PTZ). ...